Maternal Employment and Nutritional Status of Preschool Children - Yasmeen, Wahida; Rahman, Md. Motiur; Asaduzzaman, H. M; Sultana, Hafiza; Saha, Tanmoy; Jinia, Syeda Tahmina Ferdous; Alom, Foisal Mahammad Mosiul; Ahmed, Syed (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: The early childhood development is most crucial and the mother’s care and attention is essential. The purpose of the study was to compare the nutritional status of preschool children between employed and unemployed mothers. Subjects and Method: The comparative cross-sectional study was conducted among 400 children aged fewer than five years with their respondents. The study was conducted in the urban community of Rajshahi city from January, 2018 to December, 2018. The dependent variables were nutritional status of preschool children. The independent variables were socio-demographic characteristics and maternal employment. Respondents were selected by a purposive sampling method and data were collected by semi-structured questionnaire by face-to-face interview. Nutritional status was determined by anthropometric measurements. The statistical analysis was conducted using SPSS version 21. The findings of the study were presented by frequency, percentage, Mean, SD and Chi square test. Results: The mean ages of the employed and unemployed mothers were Mean= 30.79; SD=2.99 and Mean= 30.58; SD= 2.89 years respectively. Most of the employed mothers (91.0%) practiced exclusive breast-feeding for 6 months. Among the unemployed mothers, 64.0% practiced, which was a high statistical difference (p <0.001). There was highly significant statistical difference among mothers of two groups regarding starting complementary feeding as p=0.004. There was no significant statistical difference regarding children’s mid upper arm circumference (MUAC) classification. Weight for age (WAZ) - score, height for age (HAZ)-score and weight for height (WHZ)-score of employed and unemployed mother’s children showed a significant difference (p<0.05). Conclusion: Maternal employed status plays an essential role in determining child health care practice, which may influence a child’s health and development in later life. Keywords: childhood nutrition, maternal employment, stunting, underweight, wasting. Correspondence: Md. Motiur Rahman, Out Patient Department (OPD), Upazila Health Complex, Muksudpur, Gopalganj, Banhladesh. Email: motiuramc21@gmail.com. Mobile: 01937121255.